2019
DOI: 10.18632/aging.102448
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HIF1A-AS2 promotes osteosarcoma progression by acting as a sponge of miR-129-5p

Abstract: Increasing studies have demonstrated that long noncoding RNAs (lncRNAs) play vital roles in tumor development and progression. However, the relationship between osteosarcoma and HIF1AAS2 remains unknown. The expression of HIF1AAS2 and miR-129-5p was detected in osteosarcoma cell lines and samples via qRT-PCR. Cell Counting Kit-8 (CCK-8) and invasion assays were performed to determine cell proliferation and invasion ability, and a dual luciferase reporter assay was performed to determine the interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…21 HIF1A-AS2 was also found to sponge several miRNAs, such as miR-129-5p, miR-548c-3p and miR-665. 12,22,23 In our study, we demonstrated that HIF1A-AS2 interacted with miR-153-5p. We showed that miR-153-5p expression was upregulated after HIF1A-AS2 knockdown, and HIF1A-AS2 level was negatively correlated with miR-153-5p expression in NSCLC tissues.…”
Section: Dovepresssupporting
confidence: 55%
See 2 more Smart Citations
“…21 HIF1A-AS2 was also found to sponge several miRNAs, such as miR-129-5p, miR-548c-3p and miR-665. 12,22,23 In our study, we demonstrated that HIF1A-AS2 interacted with miR-153-5p. We showed that miR-153-5p expression was upregulated after HIF1A-AS2 knockdown, and HIF1A-AS2 level was negatively correlated with miR-153-5p expression in NSCLC tissues.…”
Section: Dovepresssupporting
confidence: 55%
“…19 HIF1A-AS2 has been reported to participate in several cancers, such as osteosarcoma, bladder cancer, breast cancer and colorectal cancer. [12][13][14][15] Its function in NSCLC has yet to be described. Loss-of-function assays indicated that HIF1A-AS2 knockdown suppressed proliferation, migration and invasion while inducing apoptosis.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 19 , 20 miRNAs bind complementary target mRNAs, resulting in mRNA translational inhibition and/or degradation. 21 miRNA dysregulation is detected in human OS, 22 , 23 , 24 associated with OS tumorigenesis, progression, and therapy resistance. 25 , 26 Here we identify a MAFG-targeting miRNA: microRNA-4660 (miR-4660).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs directly bind to the 3' untranslated region (3'-UTR) of the complementary mRNAs, thereby inhibiting mRNA translation and/or inducing degradation of targeted mRNAs [8,9]. Dysregulation of miRNAs is commonly detected in human OS [10][11][12], associated with OS tumorigenesis, pathogenesis and progression [8,9].…”
Section: Introductionmentioning
confidence: 99%